Avalia??o da utiliza??o de residuo de vidro de garrafas na produ??o de argamassa - Lordelo, Rodrigo Seixas Dourado (2018)
The use of waste incorporated in building materials has been pointed out as an alternative for more adequate disposal of solid waste. Among the wastes generated in Brazil, are the glass. Less than half of the glass bottles produced in Brazil are recycled. In the present work the influence of the use of waste glass of brown bottles, crushed, as partial substitute of the natural sand, in the production of mortars was evaluated. The substitution contents evaluated were 10, 20 and 30%, by mass, in addition to the reference mortar (without waste glass). The properties of the mortars in the fresh state were evaluated (workability, specific mass and incorporated air content) and also in the hardened state (flexural tensile strength, compressive strength, water absorption, void index, specific mass and alkali-silica reactivity). The results of the tests indicated that the use of waste glass bottles, replacing the natural aggregate, did not alter the fluidity of the mortars, but decreased the density and increased the content of incorporated air. The incorporation of the waste provided an increase in the tensile strengths in flexion and compression, in relation to the reference mortar. With respect to the possible alkali-silica reactivity, it was verified that the mortars with the waste glass bottle did not exceed the expansion limit established in accordance with NBR 15577-4 (ABNT, 2009). Based on the results it was concluded that it is possible to use up to 30% of waste glass of brown bottles, replacing the natural sand.